The effectiveness of social skills training (SST) for juvenile delinquents: a meta-analytical review - Stouwe, Trudy van der (Journal of experimental criminology, 2021)
To examine the effectiveness of social skills training (SST) for juvenile offenders and for whom and under which conditions SSTs are the most effective., Multilevel meta-analyses were conducted to examine the effectiveness of juvenile offender SST compared to no/placebo treatment and alternative treatment on offending, externalizing problems, social skills, and internalizing problems., Beneficial effects were only found for offending and social skills compared to no/placebo treatment. Compared to alternative treatment, small effects on only reoffending were found. Moderator analyses yielded larger effects on offending, with larger post-treatment effects on social skills. Effects on externalizing behavior were only reported in the USA, and effects on social skills were larger when the outcomes were reported through self-report., SST may be a too generic treatment approach to reduce juvenile delinquency, because dynamic risk factors for juvenile offending are only partially targeted in SST.